PREFERENSI PAKAN DI HUTAN DAN PADANG RUMPUT Rusa timorensis Blainville 1822 DI PULAU PEUCANG TAMAN NASIONAL UJUNG KULON - Sudibyo, Mufti (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2015)
Rusa timorensisis native wildlife Indonesia which have protected status that require attention in order to preserve and utilization. This study aimed to preference level of the type of diet, and mineral nutrient content of feed in the conservation area Peucang Island. Data collection was performed by following the daily movement of deer and record all types of plants are edible. Neu indexes was used to scoring of level feed,chi square test was used to distinguish in the level of preference, and inspection of feed nutrients and minerals was done in the laboratory animal science. The results showed Cynodon dactylon, Axonopus compressus, Hibiscus tiliaceus, Dendrolobium umbellatum, Lagerstroemiawhere the types of feed most preferred by the index value of the preference of feed w> 1, there where differences in the choice of feed indicated by the chi-square test Ï2count = 23.1850> Ï2 (0:05, 10) = 18:31, nutritional value and mineral feed in the forests and grasslands showed no significant difference (p> 0.05). Deer in Peucang have a tendency to choose the type of feed that contains the same nutrients and minerals between feed in the forest or grassland although of a different kind.